THE CONNECTED OF THE SUPREME COURT DECISION NUMBER 109/PK/PDT/2022 WITH THE BASIC AGRARIAN LAW NUMBER 5 OF 1960 CONCERNING EIGENDOM VERPONDING - Noor, Aslan; Herlani, Lisa; Fathurrohman, Mohammad Faridz; Lorenza, Melinda; Nurwidianti, Maudy (Legal Standing : Jurnal Ilmu Hukum, 2024)
The aim of this research is to analyze the juridical nature of the Supreme Court's decision regarding Eigendom Verponding. Ownership rights are the strongest and most hereditary land to be enjoyed fully and to control the object freely, unless this can be proven to be reversed. This research used normative research with a statutory approach. The legal materials used were primary legal materials and secondary legal materials, with legal material collection techniques through literature studies and analysis techniques. The research results indicate that judge's considerations deviate from the stipulation outlined well as statutory regulations. The emergence of multiple land ownership rights leads to criminal acts caused by negligence on the part of the land owner or parties who commit fraud, such as parties who acknowledge the land but do not, so the BPN issues a certificate. This proves the importance of creating a new policy regarding land registration through additional evidence. Ownership, and shorten the land registration process so that land owners feel energized about the lengthy process. The importance of policies regarding the formulation of criminal acts regarding certificates issued because so far, many holders of land title certificates have suffered losses as a result of the cancellation of land title certificates, overlapping ownership, and disputes originating from errors in the process.